2021
DOI: 10.3390/s21248233
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Solutions for Underwater Capacitive Power Transfer

Abstract: Capacitive power transfer (CPT) has attracted attention for on-road electric vehicles, autonomous underwater vehicles, and electric ships charging applications. High power transfer capability and high efficiency are the main requirements of a CPT system. This paper proposes three possible solutions to achieve maximum efficiency, maximum power, or conjugate-matching. Each solution expresses the available load power and the efficiency of the CPT system as functions of capacitive coupling parameters and derives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In a previous work [8], we showed that both the power transfer capability and the system's efficiency are a function of the admittance Y 12 . Increasing the mutual capacitive coupling can enhance the power transfer capability and the system's efficiency.…”
Section: Underwater Capacitive Chargingmentioning
confidence: 92%
“…In a previous work [8], we showed that both the power transfer capability and the system's efficiency are a function of the admittance Y 12 . Increasing the mutual capacitive coupling can enhance the power transfer capability and the system's efficiency.…”
Section: Underwater Capacitive Chargingmentioning
confidence: 92%
“…In the field of underwater energy transfer, some CWPT models and prototypes have already been tested in academic studies [80][81][82][83][84][85][86][87][88][89][90][91][92][93]. In most of these works, CWPT systems achieved a power transfer efficiency beneath 70% in seawater environments.…”
Section: Capacitive Wireless Power Transfermentioning
confidence: 99%
“…More recently, in a paper by Mahdi et al [92], authors studied the maximum power capability of a CWPT system by using network theory to then experimentally test it with a prototype in seawater. They were able to achieve an efficiency of 83% for a 100 mm gap and 300 kHz.…”
Section: Capacitive Wireless Power Transfermentioning
confidence: 99%
“…In the literature, studies can be found on dielectric properties of water or skin and their behavior in a CPT system. However, these kind of studies are limited to low power transfer of less than 130 W [14][15][16][17]. Despite the profound knowledge on dielectric materials for capacitors, to the best knowledge of the authors, little is known about media different from air for CPT applications with 100 W or more.…”
Section: Introductionmentioning
confidence: 99%